Affective Benefits of Nature Contact: The Role of Rumination - Bratman, Gregory N.; Young, Gerald; Mehta, Ashish; Lee Babineaux, Ihno; Daily, Gretchen C.; Gross, James J. (Frontiers in Psychology, 2021)
Mounting evidence shows that nature contact is associated with affective benefits. However, the psychological mechanisms responsible for these effects are not well understood. In this study, we examined whether more time spent in nature was associated with higher levels of positive affect in general, and lower levels of negative affect and rumination in general. We also conducted a cross-sectional mediation analysis to examine whether rumination mediated the association of nature contact with affect. Participants (N = 617) reported their average time spent in nature each week, as well as their general levels of positive and negative affect, and the degree to which they typically engaged in rumination in daily life. We then used structural equation modeling to test our hypotheses. Our results support the hypothesis that nature contact is associated with general levels of affect, and that rumination mediates this association for negative affect, and marginally mediates this association for positive affect.